Transcriptomic analysis to understand the nitrogen stress response mechanism in BNI-enabled wheat - Mishra, Chandra Nath; Sushma Kumari, Pawar; Sharma, Swati; Thakur, Arun; Sabhyata, Sabhyata; Mishra, Shubham; Kumar, Satish; Gupta, Om Prakash; Joshi, Arun; Tiwari, Ratan (MDPI, 2025)
A comparative transcriptomic analysis was conducted for the nitrogen-efficient (BNI-Munal) and derivative parent Munal wheat genotypes to unravel the gene expression patterns across four nitrogen levels (0%, 50%, 75%, and 100%). Analyzing the genes of BNI-enabled wheat helps us understand how they are expressed differently, which heavily influences BNI activity. Grain yield and 1000-grain weight were higher in BNI Munal than in Munal. All the other traits were similar in performance. Varying nitrogen dosages led to significant differences in gene expression patterns between the two genotypes. Genes related to binding and catalytic activity were prevalent among molecular functions, while genes corresponding to cellular anatomical entities dominated the cellular component category. Differential expression was observed in 371 genes at 0%N, 261 genes at 50%N, 303 genes at 75%N, and 736 genes at 100%N. Five unigenes (three upregulated and two downregulated) were consistently expressed across all nitrogen levels. Further analysis of upregulated unigenes identified links to the NrpA gene (involved in nitrogen regulation), tetratricopeptide repeat-containing protein (PPR), and cytokinin dehydrogenase 2. Analysis of downregulated genes pointed to associations with the Triticum aestivum 3BS-specific BAC library, which encodes the NPF (Nitrate and Peptide Transporter Family) and the TaVRN gene family (closely related to the TaNUE1 gene). The five unigenes and one unigene highlighted in the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways were validated in Munal and BNI Munal. The results obtained will enhance our understanding about gene expression patterns across different nitrogen levels in BNI wheat and help us breed wheat varieties with the BNI trait for improved NUE.